Empowering rural communities through hydrothermal diaper waste processing: A CSR initiative by Pertamina Patra Niaga in South Sulawesi - Saswini, Andi Ade Ula; Haris, Muhammad; Hermawan, Panji Triyanu; Rauf, Nur Inayah (Sociality: Journal of Public Health Service, 2025)
Improper management of disposable diaper waste remains a persistent environmental concern, especially in rural areas where public awareness and infrastructure are limited. Previous studies have often overlooked community-based educational interventions focused on diaper waste processing. This study aims to improve community knowledge on waste separation and disposable diaper waste management through a targeted empowerment program in Kelurahan Tamalabba, South Sulawesi. Conducted as part of the CSR initiative of PT Pertamina Patra Niaga IT Makassar, the program involved 20 residents of RW 4 and employed a combination of socialization, interactive discussions, and hands-on training. Baseline data revealed only 20% of participants had good knowledge of diaper waste handling. Following the intervention, this figure increased to 75%, indicating a substantial improvement. This study demonstrates the effectiveness of hydrothermal technology as a feasible solution for diaper waste processing in rural settings, while simultaneously emphasizing the role of participatory education in fostering environmental responsibility. These findings highlight the potential of localized CSR-supported programs to enhance public health outcomes by addressing unmanaged sanitary waste in underserved areas.